DEVELOPMENT OF DIGITAL PHYSICS MODULE (DPM) BASED ON DISCOVERY LEARNING IN THE CONCEPT OF PARABOLIC MOTION: PENGEMBANGAN DIGITAL MODULE PHYSICS (DMP) BERBASIS DISCOVERY LEARNING PADA KONSEP GERAK PARABOLA - Irsya Affiyani Darlestia; Firmanul Catur Wibowo; Esmar Budi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2025)
In today’s technological era, gadgets have become a necessity in life, one of which is in theworld of education, which can make it easier for teachers and students in the learning process. Therefore, this research aims to produce learning media in the form of digital physics modules based on Discovery Learning on the concept of parabolic motion. The method used in this research is the Research and Development (R&D) methodwith the ADDIE approach which includes five development stages, namely Analysis, Design, Development, Implementation and Evaluation. Based on the results of the needs analysis, as many as 76.9% of students are interested in using digital modules as learning resources. This research will be validated by media experts and material experts, after which it will be tested by teachers and high school students in the form of a questionnaire. It is recommended that the product of this research can be used as a valid learning medium for physics learning in class to understand the concept of parabolic motion.